An Unusual Case of Adult-Onset Still’s Disease with Hemophagocytic Syndrome, Necrotic Leukoencephalopathy and Disseminated Intravascular Coagulation - Rajaie Namas; Naveen Nannapaneni; Malini Venkatram; Gulcin Altinok; Miriam Levine; J. Patricia Dhar (Case Reports in Rheumatology)
Case. A 34-year-old African-American female with a history of adult-onset Still’s disease presented to an outside hospital with oligoarthritis. She experienced a generalized tonic-clonic seizure en route via ambulance, was intubated upon arrival, and transferred to the intensive care unit for treatment of suspected pneumonia and sepsis. She subsequently developed generalized cutaneous desquamation that progressed despite the cessation of antibiotics and other potential offending drugs which required transfer to our hospital’s burn unit. She was suspected to have reactive hemophagocytic syndrome based on her clinical presentation of fever, rash, polyarthritis, elevated liver enzymes, coagulopathy, splenomegaly, normocytic anemia, thrombocytopenia, hypertriglyceridemia, hyperferritinemia, and hemophagocytosis visualized in bone marrow biopsy specimen. Magnetic resonance imaging demonstrated necrotic demyelination of the deep white matter and corona radiata. The patient developed multiorgan dysfunction and DIC without any other attributable etiology. Despite aggressive broad spectrum therapy and high dose of steroids she progressively deteriorated and eventually expired. Conclusion. Previous publications have highlighted the prevalence of necrotic leukoencephalopathy in children with familial hemophagocytic syndrome. Our patient demonstrated some uncommon features complicating her HLH including DIC and necrotic leukoencephalopathy, which are very rare entities in AOSD.